Adenoma Detection Rate and Risk of Colorectal Cancer and Death - Corley, Douglas A; Jensen, Christopher D; Marks, Amy R; Zhao, Wei K; Lee, Jeffrey K; Doubeni, Chyke A; Zauber, Ann G; de Boer, Jolanda; Fireman, Bruce H; Schottinger, Joanne E; Quinn, Virginia P; Ghai, Nirupa R; et al. (The New England journal of medicine, 2014)
The proportion of a physician's screening colonoscopies that detect at least one adenoma (the adenoma detection rate) is a quality measure. In this study involving 136 gastroenterologists, the adenoma detection rate was inversely associated with patients' risk of interval colorectal cancer. Colonoscopy is a commonly used primary or follow-up screening test to detect colorectal cancer, 1 – 3 the second leading cause of death from cancer in the United States. 4 , 5 Colonoscopy can reduce the risk of death from colorectal cancer through detection of tumors at an earlier, more treatable stage and through removal of precancerous adenomas. 3 , 6 Conversely, failure to detect adenomas during colonoscopy may increase the subsequent risk of cancer. The adenoma detection rate, the proportion of screening colonoscopies performed by a physician that detect at least one histologically confirmed colorectal adenoma or adenocarcinoma, has been recommended as a quality benchmark . . .